2015
DOI: 10.1038/emm.2014.95
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan promotes osteoblast differentiation via JNK- and ERK-dependent BMP2–Smad 1/5/8 signaling in human mesenchymal stem cells

Abstract: Fucoidan has attracted attention as a potential drug because of its biological activities, which include osteogenesis. However, the molecular mechanisms involved in the osteogenic activity of fucoidan in human alveolar bone marrow-derived mesenchymal stem cells (hABM-MSCs) remain largely unknown. We investigated the action of fucoidan on osteoblast differentiation in hABM-MSCs and its impact on signaling pathways. Its effect on proliferation was determined using the crystal violet staining assay. Osteoblast di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
109
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 35 publications
3
109
2
2
Order By: Relevance
“…On the other hand, TGF/Smad signaling also plays an essential role in both the chondrocyte-like cell differentiation and cartilaginous tissue development (Li et al, 2005;van der Kraan et al, 2009). Several studies proposed the crosstalk between MAPK/ERK and TGF/Smad signaling, and the activation of non-canonical TGF-b signaling by ERK (Boye et al, 2015;Kim et al, 2015;Liu et al, 2014;Ottley & Gold, 2014). In this study, the phosphorylation of Smad3 partly decreased by U0126 in condition of TGF-b3 only or combined with IGF-1, and totally inhibited in IGF-1 treatment.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, TGF/Smad signaling also plays an essential role in both the chondrocyte-like cell differentiation and cartilaginous tissue development (Li et al, 2005;van der Kraan et al, 2009). Several studies proposed the crosstalk between MAPK/ERK and TGF/Smad signaling, and the activation of non-canonical TGF-b signaling by ERK (Boye et al, 2015;Kim et al, 2015;Liu et al, 2014;Ottley & Gold, 2014). In this study, the phosphorylation of Smad3 partly decreased by U0126 in condition of TGF-b3 only or combined with IGF-1, and totally inhibited in IGF-1 treatment.…”
Section: Discussionmentioning
confidence: 58%
“…It has been reported that osteoblast differentiation is induced by c-Jun N-terminal kinase and extracellular signal-related kinase-dependent BMP2-Smad 1/5/8 signaling in human mesenchymal stem cells (32). Cytokines such as TNF-α have a dual action in bone formation and are important in various skeletal diseases, including rheumatoid arthritis, inflammation and osteolysis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signals, such as growth/hormone factor stimulation and matrix-integrin binding, activate the Erk pathway in bone. Activated Erk promotes calvarial osteoblast differentiation through the downstream transcription factor Runx2 at Ser 301 and Ser 319 residues, and the mRNA levels of specific osteoblast differentiation-related marker genes are increased123456.…”
mentioning
confidence: 99%